WANPRESTASI DALAM PERSPEKTIF KEBEBASAN BERKONTRAK: ANALISIS YURIDIS TERHADAP PERLINDUNGAN HAK-HAK PARA PIHAK DALAM HUKUM PERJANJIAN - Siregar, Dahris (Rechtsregel : Jurnal Ilmu Hukum, 2025)
Analyzing the connection between default and the freedom of contract concept in Indonesian treaty law is the goal of this study. As long as it doesn't go against the law, reasonable standards, or public order, the freedom of contract concept gives the parties the opportunity to negotiate terms that suit their interests. However, in practice, there are often defaults that cause disputes and cause problems regarding the protection of the rights of the parties. This study examines how default is seen in relation to contract freedom and the degree to which the law offers parties fairness and clarity using a normative juridical technique that combines a conceptual and legislative approach. The study's findings demonstrate that contractual flexibility is constrained by legal standards that govern the legal ramifications of default. Thus, in order to prevent misuse of the concept of freedom of contract and to ensure that the agreement's goal is still accomplished, the protection of the parties' rights must be balanced.